(untitled) (Economic studies journal, 2024)
This study aimed to identify the impact of transformational leadership on organizational innovation in private health centers of Zawia city. In order to achieve the objectives of the study, the study followed the descriptive analytical method, where the study used a questionnaire to collect data, the questionnaire have been distributed to (140) employees who working in private health centers of Zawia city, and the collected questionnaire were (133), representing (94%). A valid statistical analysis form and analysis of the study data was used e-Computer and use a statistical program from the software package contained in SPSS and according to percentages and averages arithmetic and standard multiple regression analysis and One-way analysis of variance, the study have reached many results, the most important of these results are the level of dimensions of transformational leadership in private health centers of Zawia city were average, and the level of organizational innovation were average, and there is a statistically a significant effect between dimensions of transformational leadership and organizational innovation (Adoption Innovation and Innovation Abilities) in private health centers of Zawia city, in the light of these results which the study reached, the study presented a number of recommendations